The Mediating Role of Micro- and Meso-Level Factors in the Relationship between University Students' Self-Regulated Learning and Problem-Solving Skills - Esti Zaduqisti; Ali Mashuri (Psympathic : Jurnal Ilmiah Psikologi, 2026)
This study aimed to elucidate problem-solving skills in relation to self-regulated learning (SRL) among university students. The roles of emotional intelligence, academic self-efficacy, teacher charismatic leadership, and classmates' support were examined as mediators of SRL contribution to explaining problem-solving skills. A correlational design, including 224 respondents as participants, was adopted through an online questionnaire. This study analyzed the data using PROCESS installed in SPSS version 29. The results showed that SRL, academic self-efficacy, teacher charismatic leadership, and classmate support played a significant role in improving problem-solving skills. Furthermore, SRL significantly and positively predicted emotional intelligence, academic self-efficacy, teacher charismatic leadership, and classmate support. All variables exhibited significant mediating effects on the relationship between SRL and the enhancement of problem-solving skills, with the exception of emotional intelligence, academic self-efficacy, teacher charismatic leadership, and classmate support. This study contributed to the development of educational psychology by examining the roles of academic self-efficacy, teacher charismatic leadership, and classmate support as important mechanisms that explained how SRL positively affected problem-solving skills, while emotional intelligence did not act as a mediator.